Radioprotective Effect of Sodium Selenite on Mandible of Irradiated Rats - Yamasaki,Mayra Cristina (2019)
Abstract The purpose of this study was to test the radioprotective effect of selenium in the bone microarchitecture of irradiated rats mandibles. Forty rats were separated into 4 groups with 10 animals: control group (CG), irradiated group (IG), sodium selenite group (SSG) and sodium selenite irradiated group (SSIG). A single dose of 0.8 mg/kg sodium selenite was administered intraperitoneally in the SSG and SSIG groups. One hour later, animals of IG and SSIG groups were irradiated with 15 Gy of x-rays. Forty days after radiation a bilateral extraction of the mandibular first molars was performed. After the extraction procedure, five rats were killed after fifteen days and others five after thirty days. Micro- computed tomography was used to evaluate cortical and trabecular bone of each rat. The mean and standard deviation of each bone microarchitecture parameter were analyzed using the statistical test of two-way Analysis of Variance (ANOVA). At 15 days, the bone volume presented higher values in the CG and SSG groups (p=0.001). The same groups presented statistically significant higher values when bone volume fraction (p<0.001) and trabecular thickness (p<0.001) were analyzed. At 30 days, it was observed that in relation to the bone volume fraction, SSG group presented the highest value while SSIG group had the lowest value, with statistically significant difference (p=0.016). Sodium selenite demonstrated a median radioprotective effect in the bone microarchitecture of irradiated mandibles, which indicates the substance may be a potential radioprotective agent against chronic effects of high doses of ionizing radiation.